2015
DOI: 10.1371/journal.pgen.1005578
|View full text |Cite
|
Sign up to set email alerts
|

The GTP- and Phospholipid-Binding Protein TTD14 Regulates Trafficking of the TRPL Ion Channel in Drosophila Photoreceptor Cells

Abstract: Recycling of signaling proteins is a common phenomenon in diverse signaling pathways. In photoreceptors of Drosophila, light absorption by rhodopsin triggers a phospholipase Cβ-mediated opening of the ion channels transient receptor potential (TRP) and TRP-like (TRPL) and generates the visual response. The signaling proteins are located in a plasma membrane compartment called rhabdomere. The major rhodopsin (Rh1) and TRP are predominantly localized in the rhabdomere in light and darkness. In contrast, TRPL tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 68 publications
0
9
0
Order By: Relevance
“…(E) Immunocytochemical analysis on ommatidial cryosections from 1-3 day old flies was performed at well described time points of TRPL translocation (dark, 2 hr orange light, 16 hr orange light). 1,17,30 Cross sections through ommatidia are shown, except for row three which shows longitudinal sections for better visualization of TRPL vesicles. Cytoskeleton of rhabdomeres was visualized by Alexa Fluor 546 conjugated phalloidin (magenta).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…(E) Immunocytochemical analysis on ommatidial cryosections from 1-3 day old flies was performed at well described time points of TRPL translocation (dark, 2 hr orange light, 16 hr orange light). 1,17,30 Cross sections through ommatidia are shown, except for row three which shows longitudinal sections for better visualization of TRPL vesicles. Cytoskeleton of rhabdomeres was visualized by Alexa Fluor 546 conjugated phalloidin (magenta).…”
Section: Resultsmentioning
confidence: 99%
“…Electroretinogram measurements were performed as described previously. 30 In brief, 12-day old flies were immobilized in improvised yokes made from pipette tips, before they were mounted in the center of a Faraday cage. Chlorinated silver wires were inserted into glass micropipettes filled with Davenport solution (100 mM NaCl 2 , 2 mM KCl, 1 mM CaCl 2 , 1.8 mM NaHCO 3 , pH 7.2) and utilized as electrodes.…”
Section: Methodsmentioning
confidence: 99%
“…Immunocytochemistry of fly eyes was carried out as described previously (66) except that sections were additionally incubated after fixation on a shaker in 0.5% Triton X-100 in PBS (175 mM NaCl, 8 mM …”
Section: Methodsmentioning
confidence: 99%
“…By way of labeling the repeating structure of ommatidia and the PRCs within them, FPs are highly useful to evaluate a possible impact of mutations on cell morphology, especially with respect to defects in the structure or spatial orientation of rhabdomeres. As reporters in the Drosophila eye, fusion proteins of GFP with different rhabdomerally located proteins such as rhodopsins, the ion channels TRP and TRPL, the signal regulator Arrestin 2 (Arr2) or the tail domain of the NINAC isoform p174 have been generated and expressed in PRCs (Figure 4) [25][26][27][28][29]. As sensory receptor cells, PRCs are highly specialized and precise regulation of their homeostasis is required in order to ensure proper functionality.…”
Section: Using Fluorescent Proteins To Detect Structural and Protein Translocation Defects In Genetic Screensmentioning
confidence: 99%
“…TRPL::GFP had been utilized in a genetic screen with the chemical mutagen ethyl methane sulfonate (EMS) to uncover components that are involved in membrane protein trafficking. This approach resulted in the isolation of 15 TRPL translocation defective (TTD) mutants and the detailed characterization of the P-Loop-containing, GTP-and phospholipid-binding protein TTD14 [28,33]. Following an RNA-seq screen, another study reported the importance of a CUB and LDLa domain protein (CULD) for endocytic turnover of both Rh1::GFP and TRPL::GFP within Drosophila's PRCs [34].…”
Section: Using Fluorescent Proteins To Detect Structural and Protein Translocation Defects In Genetic Screensmentioning
confidence: 99%